A Comprehensive Study of Security in Cloud Computing - Chahal, Deepak; Kharb, Latika; Bhardwaj, Akash; Singla, Diksha (International Journal of Engineering and Technology, 2018)
Cloud computing has become a popular model for reducing cost of business, improvise quality of services, and provide good & secure computing. It acts as a spectrum of substantial interest among IT professionals, technocrats & business leaders due to these proven potentials. Numerous emerging computing paradigms a.k.a database outsourcing serves as future advantages of cloud computing. With the in-creasing speed of its popularity, many security questions are arising with their respective solutions aiming to give a better understanding of their complex scenario, in this paper we will provide a comprehensive view over security in context of cloud computing and also provide a view of current status of security at present. To start with, we'll take a look at various Cloud computing models, cloud computing deploy-ment models, key issues in security along with challenges in provocation of permissions to various platforms.Â Â